Dissecting Abdominal Aortic Aneurysm Is Aggravated by Genetic Inactivation of LIGHT (TNFSF14) - Andrea Herrero-Cervera (MDPI AG, 2021)
Abdominal aortic aneurysm (AAA), is a complex disorder characterized by vascular vessel wall remodeling. LIGHT (TNFSF14) is a proinflammatory cytokine associated with vascular disease. In the present study, the impact of genetic inactivation of Light was investigated in dissecting AAA induced by angiotensin II (AngII) in the Apolipoprotein E-deficient (Apoe−/−) mice. Studies in aortic human (ah) vascular smooth muscle cells (VSMC) to study potential translation to human pathology were also performed. AngII-treated Apoe−/−Light−/− mice displayed increased abdominal aorta maximum diameter and AAA severity compared with Apoe−/− mice. Notably, reduced smooth muscle α-actin+ area and Acta2 and Col1a1 gene expression were observed in AAA from Apoe−/−Light−/− mice, suggesting a loss of VSMC contractile phenotype compared with controls. Decreased Opn and augmented Sox9 expression, which are associated with detrimental and non-contractile osteochondrogenic VSMC phenotypes, were also seen in AngII-treated Apoe−/−Light−/− mouse AAA. Consistent with a role of LIGHT preserving VSMC contractile characteristics, LIGHT-treatment of ahVSMCs diminished the expression of SOX9 and of the pluripotency marker CKIT. These effects were partly mediated through lymphotoxin β receptor (LTβR) as the silencing of its gene ablated LIGHT effects on ahVSMCs. These studies suggest a protective role of LIGHT through mechanisms that prevent VSMC trans-differentiation in an LTβR-dependent manner.